AN ERROR ANALYSIS ON ENGLISH GERUNDS MADE BY THE SIXTH SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF UNIB IN THE ACADEMIC YEAR OF 2017/2018 - Recci Nuzirwan; Imranuddin .; Arasuli . (Universitas Bengkulu, 2018)
The objectives of this research are to find out the types of errors and the most dominant error of using gerunds (as a subject of a sentence, as an object of preposition or after pr eposition, as a direct object of certain verbs, after a special expression and as a passive form) by the sixth semesterstudents of English Education Study Program of UNIB in the academic year of 2017/2018. The sample of this research consisted of 77 students. This research used descriptive quantitative method. The result of the analysis shows that the students made errors in all five types of gerunds. There were 27.1% (809) errors of using gerund as direct object of certain verbs, 24.5% (735) errors of using gerund as passive form, 20.8% (624) errors of using gerund after special expression, 15.5% (463) errors of using gerund as object of preposition or after preposition, 12.1% (361) errors of using gerund as subject of a sentence. Evidently, the most dominant errors made by the students of using gerund were the gerunds as direct object of certain verbs.